Inner mitochondrial membrane protein MPV17 mutant mice display increased myocardial injury after ischemia/reperfusion - Madungwe, Ngonidzashe B (Am J Transl Res, 2020)
MPV17 is an inner mitochondrial membrane protein whose mutation results in mitochondrial DNA (mtDNA) depletion diseases such as neurohepatopathy. MPV17 is expressed in several organs including the liver and kidneys. Here, we investigated its role and mechanism of action in cardiac ischemia/reperfusion (I/R) injury. Using isolated hearts from wild type and Mpv17 mutant (Mpv17(mut)) mice, we found that mtDNA levels and normal cardiac function were similar between the groups. Furthermore, reactive oxygen species (ROS) generation, mitochondrial morphology, and calcium levels required to trigger mitochondrial permeability transition pore (mPTP) opening were all similar in normal/non-ischemic animals. However, following I/R, we found that mutant mice had poorer cardiac functional recovery and exhibited more mitochondrial structural damage. We also found that after I/R, Mpv17(mut) heart mitochondria did not produce more ROS than wild type hearts but that calcium retention capacity was gravely compromised. Using immunoprecipitation and mass spectrometry, we identified ATP synthase, Cyclophilin D, MIC60 and GRP75 as proteins critical to mitochondrial cristae organization and calcium handling that interact with MPV17, and this interaction is reduced by I/R. Together our results suggest that MPV17 has a protective function in the heart and is necessary for recovery following insults to the heart.